The Effect of Psychological Intervention on the Visual Quality of Patients with a Diffractive Multifocal Intraocular Lens Implant - Wang, Yan-Xi; Kang, Gang-Jin; Zhou, Juan; Chen, Ying; Peng, Zheng-Hong (Klinische Monatsblätter für Augenheilkunde, 2023)
Objective This study aimed to investigate the effect of psychological intervention on the visual quality of patients with a diffractive multifocal intraocular lens implant and its possible mechanism.Methods Eighty-nine patients undergoing age-related cataract surgery were enrolled in the study at the Affiliated Hospital of Southwest Medical University between December 2015 and July 2017. They were randomly divided into two groups: multiple focus M1 group (n = 45) and multiple focus M2 group (n = 40). The M1 group was only given routine preoperative health education, treatment, and evaluation, while the M2 group also received psychological intervention.Results After treatment, there was no statistical difference in the uncorrected distance and near visual acuity, corrected distance and near visual acuity, or the vision and near removal rate in either of the two groups (p > 0.05). However, postoperative glare was lower in the M2 group (p < 0.05), and patient satisfaction was higher in the M2 group (p < 0.05). The M2 group had a more obvious improvement in the Symptom Checklist-90 score (p < 0.05), the serum interleukin-6 (IL-6) was lower, and the serum brain-derived neurotrophic factor (BDNF) was higher in the M2 group (p < 0.05). In addition, serum IL-6 had a negative correlation with the depression score, and serum BDNF also showed a negative correlation with the anxiety score (p < 0.05).Conclusions Psychological intervention improved the stress state of patients with age-related cataracts and diffractive multifocal intraocular lens implants, reduced the level of inflammatory factors in the body, improved the level of BDNF, reduced postoperative visual interference, and improved postoperative satisfaction.
Keywords: pediatric ophthalmology; physiological optics; glaucoma